Education quality and the new technologies - Demo, Pedro (Revista Hipótese, 2022)
There is every reason to hope that the quality of education can be improved by new technologies. After all, it is an "enchanted" world, which could, in Assmann’s words, "re-enact" education. Assmann focuses mainly on arguments of another origin, in particular of the biology and integrality of the human being), seeking to combine "competence with solidarity sensitivity". This type of argument would serve, moreover, to focus the eye on the educational commitment, which always needs to use technological references, but with these is not confused. We already know: educational software does not exist - the "educational" software is not in the technological apparatus, but in the human environmental ability.